EFFECT OF FOLIAR APPLICATION OF MORINGA LEAVES EXTRACT ON YIELD AND QUALITY OF BREAD WHEAT - J. B, Sura; Al-Hilfy, I. H. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
A field experiment was conducted at the experimental field, Dept. of Field Crops, Coll. of Agricultural Engineering Sciences, University of Baghdad, Al-Jadiriya, Iraq, during the winter seasons of 2018-2019 and 2019-2020, to study the effect of foliar application of moringa leaves extract at different stages of growth and its reflection on yield and quality of bread wheat (Triticum aestivum L.) var. Rasheed by determining best concentration and the spraying stage to raise the efficiency of production. A split plot arrangements was used according to RCBD design with three replicates, where the main plots contained three concentrations of moringa leaves extract (1/10, 1/20, 1/30), as well as control treatment (sprayed plants with water) While the sub plots contained three spraying stages (S1: tillering + elongation + booting stage , S2: elongation + booting + 100% anthesis stage, S3: booting + 100% anthesis + grain formation stage). The results showed that the concentration of 1/20 had a significant impact by giving the highest means of quality trails and grain yield 4.73 and 4.84 Mg ha-1 for both seasons. Spraying stage S1 recorded highest grain yield 4.45 and 4.56 Mg ha-1for the both seasons while the spray stage S3 recorded the highest rate of quality trails. Therefore, we recommend spraying the moringa leaves extract with concentration of 1/20 in the S1 stage for the highest grain yield while spraying it during the S3 stage to obtaine the highest protein and wet gluten percentage.